Intracorneal Inlays for the Correction of Ametropias. Issue 4 (July 2015) - Binder, Perry S.; Lin, Ling; van de Pol, Corina
Abstract : Abstract: Various materials have been placed in the corneal stroma to modify a spherical refractive error (usually hyperopic). As the surgical procedures evolved to simplify the insertion process so has the quality and biocompatibility of the implanted materials. Failures have been due to excessive inlay dimensions, bioincompatibility of the materials used, poor choice of test model, or combinations of the above. We present a thorough analysis of the history of the intracorneal inlay and the materials and techniques used up to and including the current materials and techniques available for the correction of spherical refractive errors.